STANDARISASI EKSTRAK DIETIL ETER HERBA Oxalis corniculata L. - Herwin Herwin; Aminah Hamzah (Fakultas Farmasi UMI, 2012)
A research have been conducted about standarisation of diethyl ether ekstrack Oxalis corniculata L. herb from West Sulawesi of Mamuju with a purpose standarisation of diethyl ether ekstrack Oxalis corniculata L. based on specific and non specific parameter. On the way KLT-Bioautography diethyl ether ekstrack with Rf 0.47 value to give activity to Staphylococcus aureus, Streptococcus mutans, Staphylococcus epidermidis, Salmonella thypi, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Vibrio sp, and Candida albicans. Based on standarisation to result diethyl ether ekstrack obtained that specific parameter to organoleptic fixing ekstrac is green chocolate, typically smelling, bitter feel, jell konsistance, dissolve compound rate of ethanol 95% counted 31.37%, dissolve compound rate of water counted 24.00% and non specific parameter to stipulating on water rate counted 16.66%, dusty rate counted 4.16%, sour insoluble dusty rate counted 0.41%, total determination of bacterium 10x102 koloni/g and total kapang 37x101koloni/g. Key word : Oxalis corniculata L. Herb, Standarisation of the Diethyl Ether Ekstrack, Antimicrobial